Characteristics of U.S. Acute Care Hospitals That Have Implemented Telemedicine Critical Care - Ofoma, Uchenna R. (Crit Care Explor, 2021)
OBJECTIVES: Telemedicine critical care is associated with improved efficiency, quality, and cost-effectiveness. As of 2010, fewer than 5% of U.S. hospitals had telemedicine critical care, and fewer than 10% of ICU beds were covered. We evaluated recent telemedicine critical care implementation and bed coverage rates in the United States and compared characteristics of hospitals with and without telemedicine critical care. DESIGN: Cross-sectional study of 2018 American Hospital Association Annual Survey Database. SETTING: U.S. hospitals. PATIENTS: None. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We obtained data regarding telemedicine critical care implementation, ICU capability (defined as ≥ 1 ICU bed), other hospital characteristics, and the Herfindahl-Hirschman Index, a measure of ICU market competition based on hospital referral regions. Among 4,396 hospitals (response rate 71%), 788 (17.9%) had telemedicine critical care, providing potential coverage to 27,624 (28% of total) ICU beds. Among 306 hospital referral regions, 197 (64%) had a respondent hospital with telemedicine critical care. Telemedicine critical care implementation was associated with being a nonprofit (odds ratio, 7.75; 95% CI, 5.18–11.58) or public (odds ratio, 4.16 [2.57–6.73]) compared with for-profit hospital; membership in a health system (odds ratio, 3.83 [2.89–5.08]; stroke telemedicine presence (odds ratio, 6.87 [5.35–8.81]); ICU capability (odds ratio, 1.68 [1.25–2.26]); and more competitive ICU markets (odds ratio per 1,000-point decrease in Herfindahl-Hirschman Index 1.11 [1.01–1.22]). Notably, rural critical access hospitals had lower odds of telemedicine critical care implementation (odds ratio, 0.49 [0.34–0.70]). Teaching status, geographic region, and rurality were not associated with telemedicine critical care implementation. CONCLUSIONS: About one fifth of respondent hospitals had telemedicine critical care by 2018, providing potential coverage of nearly one third of reported ICU beds. This represents a substantial increase in telemedicine critical care implementation over the last decade. Future expansion to include more rural hospitals that could benefit most may be aided by addressing hospital financial and market barriers to telemedicine critical care implementation.